2006
DOI: 10.1016/j.ejpain.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The course of high‐sensitive C‐reactive protein in correlation with pain and clinical function in patients with acute lumbosciatic pain and chronic low back pain—A 6 months prospective longitudinal study

Abstract: In this prospective longitudinal study with a follow-up of 6 months, the course of serum concentration of C-reactive protein was measured by an ultrasensitive immunoassay in 31 patients with acute lumbosciatic pain and 41 patients with chronic low back pain. High-sensitive CRP (hsCRP), pain and clinical function were assessed at ten fixed time-points during follow-up. The course of hsCRP values was assessed in relation to the course of pain and clinical function adjusting for possible confounding factors. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 47 publications
6
61
2
1
Order By: Relevance
“…We also demonstrated a similar trend among our cohort of patients with back pain. Stümer et al [23] and Gebhardt et al [24] observed a strong association between pain severity and CRP levels in patients with sciatic pain but not in those with chronic LBP. CRP-an acute phase reactant is an indicator of low grade inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…We also demonstrated a similar trend among our cohort of patients with back pain. Stümer et al [23] and Gebhardt et al [24] observed a strong association between pain severity and CRP levels in patients with sciatic pain but not in those with chronic LBP. CRP-an acute phase reactant is an indicator of low grade inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…One study found no difference in serum hs-CRP level between patients with acute disc herniation-induced lumbosciatic pain and healthy controls [9]. In the other two studies [26,45], serum hs-CRP level was higher in patients with lumbosciatic syndrome or herniated lumbar disc than in controls.…”
Section: Physical Exercise and Sportsmentioning
confidence: 96%
“…Three case-control studies [9,26,45] addressed the association between high-sensitive C-reactive protein (hs-CRP) and clinically defined sciatica (Table 5). One study found no difference in serum hs-CRP level between patients with acute disc herniation-induced lumbosciatic pain and healthy controls [9].…”
Section: Physical Exercise and Sportsmentioning
confidence: 99%
“…Just one study, Karppinen et al [29], included BMI and work load in the analyzes. Moreover, Gebhardt et al [37] controlled for smoking and BMI. In only 6 studies the data were evaluated after correction for their multiple testing.…”
Section: Resultsmentioning
confidence: 99%